Eye hydrodynamics in children subject to total intravenous anesthesia - L. S. Khamraeva; L. Yu. Bobokha; N. Sh. Akhmedova (Российский офтальмологический журнал)
Purpose: to study eye hydrodynamics in children subjected to total intravenous anesthesia during ophthalmic operations. Materials and methods. 50 children (100 eyes) aged 15 days to 14 years were examined. 21 children showed impaired hydrodynamics while the remaining 29 had no hydrodynamic disorders. All patients received combined endotracheal anesthesia for ophthalmic operations. Results. The patients with undisturbed hydrodynamics showed a significant increase in true intraocular pressure (Po) (by 3.8 ± 0.12 mm Hg) after an injection of anesthesia with ketamine, due to a significant increase in aqueous humor production. Children with disturbed hydrodynamics, who received an antihypertensive ophthalmic drug (arutimol 0.25–0.5 %), after an injection of anesthesia with fentanyl, showed a significant Po decrease (by 3.9 ± 0.12 mm Hg) due to a significant increase of outflow facility rate (C) and a decrease in aqueous humour volume (F). The patients who received no antihypertensive therapy showed a significant decrease in Po (by 2.08 ± 0.7 mm Hg) due to a significant increase in C. In contrast, the decrease in F proved to be insignificant. Conclusion. For an objective assessment of tonographic  parameters in children with impaired eye hydrodynamics who received antihypertensive therapy (arutimol 0.25–0.5 %) and anesthesized with fentanyl, we recommend that the Po indices be adjusted  upwards by 3.9 ± 0.12 mm Hg, without arutimol by 2.08 ± 0.7 mm Hg, which will help in choosing the type and volume of antiglaucomatous operations. It is also necessary to take into account the increase in Po under the action of ketamine (by 3.8 ± 0.12 mm Hg) in children with undisturbed eye hydrodynamics to prevent possible intra- and postoperative complications.